2022
DOI: 10.1007/s00408-022-00549-8
|View full text |Cite
|
Sign up to set email alerts
|

Stage I and II Small-Cell Lung Cancer—New Challenge for Surgery

Abstract: Purpose The recommended treatment for small-cell lung cancer (SCLC) currently is surgery in stage I disease. We wondered about stage II SCLC and present a meta-analysis on mean-survival of patients that underwent surgery for stage I and II compared to controls. Methods A systematic literature search was performed on December 01st 2021 in Medline, Embase and Cochrane Library. We considered studies published on the effect of surgery in SCLC since 2004 and as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Surgery is the main method of cancer treatment, although a previous trial has demonstrated that radiotherapy resulted in a better prognosis than surgery for SCLC patients before the 1970s [ 5 ]. In-depth research has allowed patients with stage I–II and even stage III N2 SCLC to be regarded as a surgical evaluation population [ [6] , [7] , [8] , [9] ]. Multiple studies have shown that the management of surgery can prolong the survival time of early-stage SCLC patients compared to those treated with concurrent chemoradiation [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Surgery is the main method of cancer treatment, although a previous trial has demonstrated that radiotherapy resulted in a better prognosis than surgery for SCLC patients before the 1970s [ 5 ]. In-depth research has allowed patients with stage I–II and even stage III N2 SCLC to be regarded as a surgical evaluation population [ [6] , [7] , [8] , [9] ]. Multiple studies have shown that the management of surgery can prolong the survival time of early-stage SCLC patients compared to those treated with concurrent chemoradiation [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…While radical surgery has proven effective for early stage SCLC patients with T1-2N0M0, it should be noted that this subset represents a mere 5% of all LS-SCLC cases, making the benefits of surgery challenging to extend beyond this limited group. [41–43] The analysis of this study showed that the rates of surgery in elderly SCLC patients with stage I–IV were 36.1%, 22.3%, 6%, and 1.1%. Overall, the early mortality rates for patients who did not receive versus those who received surgical treatment were 38.5% and 11.8%, respectively, suggesting that the risk of early death is markedly reduced in elderly SCLC patients after surgery.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, the subgroup analysis of the retrospective study showed that the OS rate of patients who received surgical treatment was higher regardless of whether they had stage I (HR: 0.56,95% CI: 0.49–0.64, p < 0.001), II (HR: 0.75, 95% CI: 0.57–0.99, p = 0.04) or III disease (HR: 0.70, 95% CI: 0.56–0.88, p = 0.002). In 2022, Doerr et al 27 conducted a meta‐analysis of 11 241 stage I–II SCLC patients in seven studies between 1984 and 2015. The results showed that the average survival time of stage I patients was 36.7 ± 10.8 months in the surgical group and 20.3 ± 5.7 months in the nonsurgical group ( p = 0.0084).…”
Section: Discussionmentioning
confidence: 99%